Sliding member

By applying copper-containing manganese phosphate coating on the steel sliding members, the problem of insufficient wear resistance in strict sliding environments is solved, environmental protection, durability and efficiency are improved, and the manufacturing process is simplified.

CN119301302APending Publication Date: 2025-01-10PARKER KAKO CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380043421.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-05-31
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The coating produced in the prior art under severe sliding environments is insufficient to wear resistance and the calcination process is complex, which affects environmental protection and efficiency.

Method used

A combined sliding member made of steel is used, and its sliding surface is coated with a copper-containing manganese phosphate coating, the manganese content is 0.89 g/m2 or more, the copper/manganese ratio is in the range of 0.03 to 2.50, and the surface roughness Ra is 0.16μm. As above, the skewness Rsk is −1.01 or less, and the coating thickness is 1.4 μm or more, and it is manufactured by a simple process.

Benefits of technology

A combined sliding member with environmentally friendly, excellent sintering resistance, wear resistance, fatigue resistance and heat release properties is realized, which simplifies the manufacturing process and reduces the amount of greenhouse-effect gas generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301302A_ABST
    Figure CN119301302A_ABST
Patent Text Reader

Abstract

Provided is a combined sliding member which has a low environmental burden, can be produced by a simple method, and has excellent durability such as sintering resistance, wear resistance, fatigue resistance, and heat release properties. The problem is solved by a combined sliding member provided with a first sliding member and a second sliding member which are formed of a steel material and slide relative to each other. Namely, a combined sliding member in which at least one of the sliding surfaces of a first sliding member and a second sliding member that slide with respect to each other has a manganese phosphate coating film containing copper, the manganese phosphate coating film having a manganese content of 0.89 g / m2 or more and a copper / manganese content ratio of 0.03-2.50, and the manganese content ratio of 0.89 g / m2 or more and the copper / manganese content ratio of 0.03-2.50. The arithmetic average roughness Ra of the surface of the base material on which the sliding surface having the manganese phosphate coating film is provided is 0.16 [mu] m or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sliding member, and more particularly to a combined sliding member including a plurality of sliding members that slide against each other. Background Art

[0002] Conventionally, a combined sliding member including a plurality of members is used. As such a combined sliding member, for example, a compressor member subjected to a chemical conversion coating treatment for improving wear resistance (Patent Document 1), a sliding member having a resin coating layer including a solid lubricant, etc. (Patent Document 2), etc. are known.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2005-351099

[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 4-175442 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The coating produced by the chemical conversion treatment of the above-mentioned prior art may not necessarily achieve sufficiently high performance such as wear resistance under severe sliding environments. In addition, for sliding components used in severe sliding environments, a calcination process is required to form a resin layer containing a solid lubricant, etc. Therefore, it is not necessarily possible to say that the sliding component has been modified by a simple method.

[0009] Furthermore, in the method for manufacturing a sliding member including a calcining step, from the viewpoint of global warming, for which countermeasures are required, a problem of reducing the amount of greenhouse gas generated in life cycle assessment has been recognized.

[0010] The present invention has been made in view of such a viewpoint, and according to the present invention, a combined sliding member can be provided which has a low environmental burden, can be manufactured by a simple method, and has excellent durability such as seizure resistance, wear resistance, and fatigue resistance, and heat dissipation properties.

[0011] Solutions for solving problems

[0012] The above-mentioned problems are solved by the present invention. The present invention includes the following technical solutions.

[0013] [1] A combined sliding member comprising a first sliding member and a second sliding member formed of a steel material and sliding against each other,

[0014] At least one of the sliding surfaces of the first sliding member and the second sliding member that slide against each other has a manganese phosphate coating containing copper, and the manganese content in the manganese phosphate coating is 0.89 g / m 2 Above, the copper / manganese content ratio is 0.03 to 2.50,

[0015] The arithmetic mean roughness Ra of the surface of the base material on which the sliding surface having the manganese phosphate film is provided is 0.16 μm or more.

[0016] [2] The combined sliding member according to [1] above, wherein the manganese phosphate coating has a thickness of 1.4 μm or more.

[0017] [3] The combined sliding member according to [1] above, wherein the skewness Rsk of the surface of the base material is not more than -1.01.

[0018] [4] The combined sliding member according to [1] above, wherein the manganese content is 2.1 g / m 2 above.

[0019] [5] The combined sliding member according to [3] above, wherein the skewness Rsk of the surface of the base material is not more than -1.78.

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to provide a combined sliding member which has a low environmental burden, utilizes a simple method, and is excellent in durability such as seizure resistance, wear resistance, and fatigue resistance, and heat dissipation properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a diagram showing an example of an SEM magnified observation image of the copper-containing manganese phosphate film in Example 3.

[0023] Figure 2 This is a diagram schematically showing the method of the Falex test (friction and wear test). DETAILED DESCRIPTION

[0024] Hereinafter, the present invention will be described in detail.

[0025] [1. Sliding member]

[0026] The combined sliding member of the present invention includes a plurality of sliding components including at least a first sliding component and a second sliding component, and the first sliding component and the second sliding component are configured so that sliding surfaces of the first sliding component and the second sliding component contact and slide with each other.

[0027] (1-1. Sliding parts)

[0028] 1-1a. Material of sliding parts

[0029] The first sliding member and the second sliding member each contain at least a steel material. The first sliding member and the second sliding member are preferably formed substantially only of a steel material.

[0030] Specific examples of steel materials included in sliding parts include alloy steels ((hereinafter represented by the steel-based material symbols specified in JIS G4805:2008) high carbon chromium bearing steels such as SUJ2, SUJ3, SUJ4, SUJ5; SCM series (chrome-molybdenum steel); SCr series (chrome steel) such as SCr420; SNCM series (nickel-chromium-molybdenum steel) etc.), carbon steels (SXXC series such as S45C etc.), and cast irons (FCD series (ductile iron) etc.).

[0031] Specific examples of SCM-based steels (chrome-molybdenum steels) include SCM415, SCM420, SCM421, SCM430, SCM432, SCM435, SCM440, SCM445, and SCM822.

[0032] In addition, as more specific examples of steel materials included in the sliding member, there can be listed steel-based material symbols SUJ1 (SUJ material: high carbon chromium bearing steel material), SCr415, SCr435 (SCr material: chrome steel material), SCM418, SCM425 (SCM material: chrome-molybdenum steel material), SNCM220, SNCM420, SNCM815 (SNCM material: nickel-chromium-molybdenum steel material), SUS440, SUS403, SUS410, SUS410 J1, SUS410F2, SUS416, SUS420J1, SUS420J2, SUS420F, SUS420F2, SUS431, SUS440A, SUS440B, SUS44 0C, SUS440F, SUS405, SUS410L, SUS430, SUS430F, SUS434, SUS447J1, SUSXM27, SUS329J1, SUS329J3L , SUS329J4L, SUS201, SUS202, SUS301, SUS302, SUS303, SUS303Se, SUS303Cu, SUS304, SUS304L, SUS 304N1, SUS304N2, SUS304LN, SUS304J3, SUS305, SUS309S, SUS310S, SUS316, SUS316L, SUS316N, SUS 316LN, SUS316Ti, SUS316J1, SUS316J1L, SUS316F, SUS317, SUS317L, SUS317LN, SUS317J1, SUS836L, SUS890L, SUS321, SUS347, SUSXM7, SUSXM15J1, SUS631, and substances specified in other standards such as AISI that roughly correspond to the above-mentioned JIS standards.

[0033] As more specific examples of the steel materials contained in the first sliding component and the second sliding component, cold rolled steel sheets (SPCC), carbon steel pipes for machine structures (STKM materials), carbon tool steels (SK materials), alloy tool steels (SKS materials), sintered materials for machine structure parts, and other special steels for structures can also be listed.

[0034] The steel material used as the material of the sliding member is preferably SCM415, SCr420, SUJ2, SNCM220 or the like.

[0035] In addition, the steel material of the sliding member may be subjected to a predetermined heat treatment, for example, quenching and tempering, carburizing, vacuum carburizing, or carbonitriding and quenching and tempering.

[0036] The first sliding member and the second sliding member may be formed of only a single type of steel material, or may include more than one type of steel material. In addition, the first sliding member and the second sliding member may be made of the same material, or may be made of different materials.

[0037] 1-1b. Copper-containing manganese phosphate coating (phosphate coating)

[0038] For at least one of the first sliding member and the second sliding member, that is, at least one sliding member, a copper-containing manganese phosphate coating is formed on the sliding surface in contact with the other sliding member. The manganese phosphate coating in the present invention can be formed on the sliding surfaces of both the first sliding member and the second sliding member, but is usually formed on only one of the first sliding member and the second sliding member. The manganese phosphate coating of the sliding member is arranged on the surface of the sliding surface in a manner of contacting the sliding surface of the sliding member as the object.

[0039] The manganese phosphate film contains copper. Specifically, copper compounds added when the manganese phosphate film is formed can be listed. Figure 1 As shown in the figure, it is a form in which copper is eutected into a manganese phosphate film containing copper. Figure 1 The SEM image of exemplifies that the copper-containing manganese phosphate coating indicated by reference numeral 12 includes co-precipitated copper 14 indicated in white and a region (manganese phosphate coating portion) 16 of the manganese phosphate coating indicated in gray.

[0040] In addition, the manganese content in the manganese phosphate film (content based on the unit area of ​​the film) is 0.89 g / m 2 The manganese content in the manganese phosphate coating is preferably 1.0 g / m 2 Above, 1.07g / m 2 or 1.1 g / m 2 Above, 1.2g / m 2 Above, 1.6g / m 2 Above, 1.8g / m 2 Above or 2.1g / m 2 In addition, the manganese content in the manganese phosphate coating is preferably 2.3 g / m 2 More preferably, 2.5 g / m 2 More preferably, 3.0 g / m 2 above.

[0041] In addition, regarding the manganese content in the manganese phosphate coating, the lower limit is important, and the upper limit is not particularly limited, and can be, for example, 15 g / m 2 Below, 10g / m 2 Below, 8g / m 2 Below or 6g / m 2 the following.

[0042] In the manganese phosphate coating, the value of the copper / manganese content ratio (weight ratio), that is, the content ratio of copper to manganese per unit area contained in the manganese phosphate coating, is, for example, in the range of 0.03 to 2.50. The above ratio of the content of copper to manganese per unit area in the manganese phosphate coating (the value of the content ratio) is preferably 0.03 or more, more preferably 0.04 or more, 0.06 or more, 0.10 or more, or 0.12 or more, further preferably 0.16 or more, and particularly preferably 0.20 or more, 0.24 or more, or 0.25 or more. In addition, the value of the content ratio is preferably 2.50 or less, more preferably 2.00 or less, 1.50 or less, 1.30 or less, 1.28 or less, 1.20 or less, 1.16 or less, 1.10 or less, 1.06 or less, or 1.04 or less, and further preferably 1.00 or less, 0.76 or less, or 0.61 or less.

[0043] The content ratio is, for example, in the range of 0.03 to 2.50, 0.03 to 2.00, 0.04 to 2.50, 0.04 to 1.50, 0.04 to 1.30, etc. In addition, the content ratio is more preferably in the range of 0.04 to 1.28, particularly preferably in the range of 0.04 to 0.76, 0.04 to 0.61, 0.06 to 1.28, 0.06 to 1.20, 0.10 to 1.20, 0.10 to 1.16, 0.12 to 1.10, 0.12 to 1.06, 0.16 to 1.04, 0.16 to 1.00, etc.

[0044] Phosphate coatings other than the manganese phosphate coating may be used, and specific examples thereof include zinc phosphate coatings, calcium zinc phosphate coatings, and zinc manganese phosphate coatings which are phosphate coatings containing manganese like the manganese phosphate coating.

[0045] As described above, in the phosphate film containing a metal other than manganese, phosphate and copper coprecipitate as in the manganese phosphate film. The range of the content of the metal derived from phosphate in the phosphate film and the weight ratio of the metal derived from phosphate to copper are the same as in the case of the manganese phosphate film.

[0046] That is, in the phosphate coating containing metals other than manganese, the total content of metals derived from phosphate is preferably 0.89 g / m 2 Above, 1.0g / m 2 Above, 1.07g / m 2 or 1.1 g / m 2 Above, 1.2g / m 2 Above, 1.6g / m 2 Above, 1.8g / m 2 Above or 2.1g / m 2More preferably 2.3 g / m 2 More preferably, 2.5 g / m 2 Above, particularly preferably 3.0 g / m 2 above.

[0047] In addition, regarding the total content of metals derived from phosphate in the phosphate coating containing metals other than manganese, the lower limit is important, and the upper limit is not particularly limited, and may be, for example, 15 g / m 2 Below, 10g / m 2 Below, 8g / m 2 Below or 6g / m 2 the following.

[0048] In a phosphate coating containing metals other than manganese, the weight ratio of copper to the total amount of metals derived from phosphate is preferably within the range of the above-mentioned content ratio. That is, the above-mentioned ratio (value of the content ratio) of the content of copper per unit area to the total amount of metals derived from phosphate is 0.03 or more, more preferably 0.04 or more, 0.06 or more, 0.10 or more, or 0.12 or more, further preferably 0.16 or more, and particularly preferably 0.20 or more, 0.24 or more, or 0.25 or more. In addition, the value of the content ratio is preferably 2.50 or less, more preferably 2.00 or less, 1.50 or less, 1.30 or less, 1.28 or less, 1.20 or less, 1.16 or less, 1.10 or less, 1.06 or less, or 1.04 or less, further preferably 1.00 or less, 0.76 or less, or 0.61 or less.

[0049] The content ratio is, for example, 0.03 to 2.50, preferably 0.03 to 2.00, 0.04 to 2.50, 0.04 to 1.50, 0.04 to 1.30, etc. In addition, the content ratio is more preferably in the range of 0.04 to 1.28, particularly preferably in the range of 0.04 to 0.76, 0.04 to 0.61, 0.06 to 1.28, 0.06 to 1.20, 0.10 to 1.20, 0.10 to 1.16, 0.12 to 1.10, 0.12 to 1.06, 0.16 to 1.04, 0.16 to 1.00, etc.

[0050] From the above, it is clear that the manganese phosphate coating contains copper co-precipitated with the formation of the manganese phosphate coating, and various phosphates may be contained as other components. For example, the phosphate coating is preferably a manganese phosphate coating, but may be a zinc phosphate coating or a zinc calcium phosphate coating. Among them, from the viewpoint of improving the adhesion and sliding properties of the phosphate coating, it is preferable to use a manganese phosphate coating or a zinc manganese phosphate coating.

[0051] The copper-containing phosphate film is formed from various phosphate solutions. For example, the copper-containing phosphate film is formed by adding a compound containing copper ions to a treatment solution appropriately adjusted using a manganese phosphate treatment agent, a zinc phosphate treatment agent, a zinc calcium phosphate treatment agent, or a zinc manganese phosphate treatment agent (all of which are preferably made by Nihon Parkerizing (e.g., PF-M1A and PF-M5 as manganese phosphate treatment agents)).

[0052] 1-1c. Copper in manganese phosphate coating (phosphate coating)

[0053] The phosphate solution preferably contains the following compound as a copper ion supply source for co-precipitating copper and phosphate.

[0054] That is, as a supply source of copper ions, in addition to copper (II) nitrate, aqueous solutions of copper (I) chloride, copper (II) chloride, copper (II) sulfate, copper (II) carbonate, copper (II) phosphate, copper (II) pyrophosphate, etc., metallic copper, etc. can be listed, and any of them can be added to the above-mentioned phosphate treatment solution, and the added treatment solution can be used to form a copper-containing phosphate film.

[0055] The copper-containing phosphate coating is formed by, for example, immersing a sliding member that has been subjected to pretreatments such as cleaning, degreasing, and surface conditioning by a common method in the mixed treatment liquid.

[0056] In the manganese phosphate coating, as described above, it is preferred that the copper / manganese content ratio is within the range of 0.03 to 2.50, and the copper / total amount of metal derived from phosphate is also adjusted to within the range of 0.03 to 2.50. Therefore, the content of the copper ion supply source contained in the phosphate solution is appropriately adjusted so as to achieve the range of the content ratio.

[0057] Additives such as a source of tin, lead, silver, and gold, which are more expensive than iron, can be added to the phosphate solution together with or in place of the source of copper ions. For example, from the viewpoint of the exothermicity of the manganese phosphate coating, as a material significantly higher than Sn having a thermal conductivity of 66.6 [W / (m·K)] and Pb having a thermal conductivity of 35.2 [W / (m·K)], in addition to Cu having a thermal conductivity of 398 [W / (m·K)], Ag having a thermal conductivity of 427 [W / (m·K)] and Au having a thermal conductivity of 315 [W / (m·K)] can also be suitably used. Among them, if the ease of acquisition, cost, etc. are also taken into consideration, it is preferred to add Cu (copper) ions to the manganese phosphate coating.

[0058] In addition, resin additives may be used together with or in place of a source of metal (metal ion) such as copper. In other words, fluorine resins (polytetrafluoroethylene, etc.) and polyolefin resins (polyethylene, etc.) of dispersion specifications that can be dispersed in a solution that is mainly an aqueous solution may also be used.

[0059] In the phosphate coating, the content ratio of the total of the additive source components derived from the copper ion supply source used as the additive to the metal derived from the phosphate such as manganese is also preferably adjusted to a range of 0.03 to 2.50. Therefore, the total content of the additives contained in the phosphate solution is also appropriately adjusted in a manner that can achieve the range of the content ratio in the phosphate coating.

[0060] (1-2. Properties and Structure of Copper-Containing Manganese Phosphate Coating (Phosphate Coating))

[0061] The thickness of the phosphate film such as the manganese phosphate film is appropriately adjusted according to the use of the sliding member, and is preferably 1.4 μm or more, 1.8 μm or more, 2.0 μm or more, 2.5 μm or more, or 3.0 μm or more. In addition, the thickness of the phosphate film such as the manganese phosphate film is, for example, 25 μm or less, 20 μm or less, 18 μm or less, or 16 μm or less. The thickness of the phosphate film is preferably 1.4 μm or more and 16 μm or less, more preferably 2.0 μm or more and 14 μm or less, and particularly preferably 3.0 μm or more and 11 μm or less.

[0062] In addition, for phosphate films such as manganese phosphate films, it is preferred that the load resistance is excellent. Specifically, in the FALEX test described later, the load resistance is evaluated by measuring the maximum load value until sintering occurs, and the sintering resistance load based on the Pin & Vee-Block friction and wear tester is preferably 10 kN or more, more preferably 15 kN or more, and particularly preferably 20 kN or more.

[0063] (1-3. Properties of sliding surface)

[0064] 1-3a. Arithmetic mean roughness: Ra value

[0065] For at least one of the first sliding member and the second sliding member, the surface roughness of the base material surface provided with the sliding surface having the manganese phosphate film is adjusted. For example, the roughness of the base material surface of the sliding member can be adjusted according to the base material reaction when the manganese phosphate film is formed, or it can be adjusted in combination with the mechanical processing performed before the chemical conversion treatment.

[0066] That is, the value of the arithmetic mean roughness Ra based on JIS B0601:2001 of the boundary surface with the manganese phosphate film in the sliding part as the base material, that is, the surface of the sliding part as the base material in a state where the manganese phosphate film is removed, is preferably 0.16 μm or more, and can be 0.18 μm or more, 0.20 μm or more, or 0.30 μm or more.

[0067] The value of the arithmetic mean roughness Ra of the surface of the base material provided with the sliding surface with the manganese phosphate film removed according to JIS B0601:2001 is, for example, 2.00 μm or less, preferably 1.80 μm or less, more preferably 1.65 μm or less, and further preferably 1.55 μm or less.

[0068] In addition, as described above, it is important to adjust the surface roughness of the parent material surface, but the value of the arithmetic mean roughness Ra of the outermost surface of the manganese phosphate coating, i.e., the sliding surface, can also be appropriately adjusted. There is no particular limitation on the method for adjusting the surface roughness of the sliding surface. The roughness can be adjusted by processes such as the parent material reaction when the manganese phosphate coating is generated, or by mechanical processing implemented before the subsequent chemical conversion treatment, or by these methods in a composite manner. For example, the arithmetic mean roughness Ra of the sliding surface can be adjusted to less than 2.00 μm based on JIS B 0601:2001. The value of the arithmetic mean roughness Ra of the sliding surface can be adjusted by grinding processing after film formation, for example, as a method for removing the convex portion of the formed manganese phosphate coating or reducing the height of the convex portion, a grinding process such as polishing grinding and honing can be implemented to achieve smoothing of the sliding surface.

[0069] In addition, since it is preferable that the surface roughness of the sliding surface is small, the lower limit of the arithmetic mean roughness Ra of the sliding surface is not so important, and the arithmetic mean roughness Ra is, for example, 0.10 μm or more.

[0070] In addition, the measuring method of the arithmetic mean roughness Ra value is described later.

[0071] 1-3b. Skewness: Rsk value

[0072] The value of the skewness (Rsk) based on JIS B0601:2001 of the surface of the base material on which the sliding surface having the manganese phosphate coating is formed, that is, the outermost surface of the sliding component in a state where the manganese phosphate coating is removed, is, for example, 0.0 or less, -0.50 or less, -1.00 or less, -1.01 or less, -1.10 or less, -1.30 or less, or -1.50 or less, preferably -1.78 or less, more preferably -2.00 or less, further preferably -2.50 or less, and particularly preferably -3.00 or less.

[0073] The value of the skewness (Rsk) of the surface of the base material after the manganese phosphate coating is removed according to JIS B0601:2001 is, for example, -4.2 or more, -4.1 or more, or -4.0 or more.

[0074] The Rsk value is the cubic average of Z(x) at the reference length that is dimensionless by the cube of the root mean square height (Rq), which represents the symmetry of the peaks and valleys when the average line of the concave and convex on the surface is the center. If the Rsk value is a negative value, it means that the valley of the surface is deep. And, as described above, in the sliding surface formed on the base material adjusted in a manner that the surface Rsk becomes a sufficiently low negative value, the oil content as a lubricant is easily accumulated in the valley, which can improve the durability of the sliding part having such a sliding surface, such as sintering resistance, wear resistance, fatigue resistance, etc.

[0075] The Rsk value of the coating surface, that is, the sliding surface, in a state where the manganese phosphate coating is formed is, for example, -1.5 to 1.5 (-1.5 or more and 1.5 or less), or -1.0 to 1.0.

[0076] It should be noted that the method for measuring the Rsk value will be described in detail later.

[0077] Generally, when a sliding member is used, heat is generated as the coating slides. Therefore, the manganese phosphate coating included in the combined sliding member preferably has excellent heat dissipation. The value of the thermal diffusivity may also vary depending on the type and thickness of the base material, but the preferred range of the value of the thermal diffusivity measured for the manganese phosphate coating is as follows.

[0078] For example, the thermal diffusivity of the manganese phosphate film measured by the method described below is preferably 21.0 (mm 2 / s) or more, more preferably 21.2 (mm 2 / s) or above or 21.4(mm 2 / s) or more, more preferably 21.5 (mm 2 / s) or above or 21.6(mm 2 / s) or more, particularly preferably 21.8 (mm 2 / s) or more, 22.0(mm 2 / s) or above or 22.1(mm 2 / s) or above.

[0079] The thermal diffusivity of the manganese phosphate coating at 100° C. is preferably 18.5 (mm 2 / s) or more, more preferably 18.6 (mm 2 / s) or above or 18.8(mm 2 / s) or more, more preferably 19.0 (mm 2 / s) or above or 19.2(mm 2 / s) or more, particularly preferably 19.3 (mm 2 / s) or more, 19.4(mm 2 / s) or above or 19.5(mm 2 / s) or above.

[0080] In addition, the thermal diffusivity of the manganese phosphate coating at 100° C. is preferably 17.0 (mm 2 / s) or more, more preferably 17.2 (mm 2 / s) or above or 17.3(mm 2 / s) or more, more preferably 17.4 (mm 2 / s) or above or 17.6(mm 2 / s) or more, particularly preferably 17.7 (mm 2 / s) or more, 17.8(mm 2 / s) or above or 17.9(mm 2 / s) or above.

[0081] (1-4. Secondary coating)

[0082] A calcined film may be further formed on a phosphate film such as a manganese phosphate film. For example, a calcined film may include an organic binder, a curing agent, a solid lubricant, etc. In order to form a calcined film, a calcining process of heating the material of the calcined film is necessary, because the calcining process also discharges carbon dioxide, which is a greenhouse gas. Therefore, if a calcined film is not formed, but only a phosphate film having a specified component such as copper is provided by a simple method as described above, the efficiency of the manufacturing process can be achieved.

[0083] In addition, secondary films that can be formed on phosphate films such as manganese phosphate films include: organic resin films that do not involve a calcination process and contain solid lubricants, etc.; organic resin films that contain solid lubricants, etc. obtained by an immersion process such as electrodeposition coating; films obtained by immersing a base material in a solution of a fluorine-based resin (polytetrafluoroethylene, etc.), a polyolefin-based resin (polyethylene, etc.), and a molybdenum compound, etc. dispersed in water and stacked, etc. Various processes are required to manufacture these secondary films, but if only a phosphate film is provided, the efficiency of the manufacturing process can be achieved.

[0084] [2. Method for manufacturing sliding member]

[0085] The first sliding component and the second sliding component can be manufactured according to known methods.

[0086] For the sliding part, the surface roughness, in particular, the roughness of the surface on which the manganese phosphate film is to be formed, is adjusted. For example, the surface roughness of the sliding part can be adjusted by a known method such as turning or lathe processing.

[0087] In addition, a phosphate coating is formed on the surface of at least one of the sliding parts by, for example, using the above-mentioned phosphate solution. In the surface of the sliding part on which the phosphate coating is to be formed, it is preferred that: the surface roughness is increased by the phosphate coating forming step, and after the coating is formed, the values ​​of Ra, Rsk, etc. are adjusted to the above-mentioned preferred ranges.

[0088] It should be noted that the surface of the sliding part that is not coated with a manganese phosphate film and that is in contact with the manganese phosphate film (hereinafter referred to as the contact surface) preferably has suppressed roughness. For example, the arithmetic mean roughness Ra of the contact surface is 2.9 μm or less or 1.9 μm or less, preferably 1.8 μm or less, more preferably 1.6 μm or less, further preferably 1.5 μm or less, and particularly preferably 1.4 μm or less, 1.3 μm or less, 1.2 μm or less, 1.1 μm or less, or 1.0 μm or less.

[0089] In addition, it is preferable that the surface roughness of the contact surface is small, and therefore the lower limit of the Ra value is not so important. The Ra value of the contact surface is, for example, 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, or 0.4 μm or more.

[0090] [3. Application of sliding components]

[0091] The above-mentioned combined sliding member is used in various applications, and is particularly widely and flexibly used in a combined sliding member including a plurality of sliding parts whose main material is steel.

[0092] For example, as the components used for the above-mentioned combined sliding component, i.e., the first sliding component or the second sliding component, there can be listed gears, bearings (such as rolling bearings, sliding bearings, etc.), cams, gaskets, barrels, pistons, rocker arms, valve lifters, bolts, nuts, washers, springs, shafts, plates, connecting rods, piston pins, spline shafts, yokes, constant velocity joints (inner ring, outer ring, cover), camshafts, and other components in which two or more iron components contact each other and slide and / or rotate.

[0093] [Example]

[0094] Hereinafter, although an Example is demonstrated, this invention is not limited to each Example.

[0095] (Preparation of Phosphate Film Forming Solution)

[0096] A treatment solution for a manganese phosphate coating containing copper was prepared by the method described below. That is, the mixing ratio of a manganese phosphate treatment agent (PF-M5: manufactured by Nihon Parkerizing Co., Ltd.) and copper (II) nitrate was appropriately adjusted to obtain the coating components of Examples 1 to 5 and Comparative Example 4 in Table 1 below, and then mixed to obtain an aqueous solution. That is, a manganese phosphate treatment solution containing copper was prepared for forming a manganese phosphate coating formed on the surface of a steel material in a combination sliding member.

[0097] (Example 1)

[0098] The outer peripheral surface of a pin-shaped SCM415 steel material (sliding component) was subjected to pretreatment such as cleaning, degreasing, and surface conditioning, and then immersed in the manganese phosphate treatment solution containing copper prepared as described above at a treatment temperature of 90° C. and a treatment time of 10 minutes to obtain a pin-shaped steel material having a copper-containing manganese phosphate coating.

[0099] (Examples 2 to 5 and Comparative Example 4)

[0100] In order to obtain the coating compositions described in Examples 2 to 5 and Comparative Example 4 in Table 1 below, pin-shaped steel materials having a copper-containing manganese phosphate coating were obtained by the same method as in Example 1 except that a manganese phosphate treatment liquid having a composition different from that in Example 1 and containing copper was used.

[0101] (Comparative Examples 1 to 3 and Comparative Example 5)

[0102] In Comparative Example 1, no manganese phosphate coating was formed, and only a pin-shaped steel material of SCM415 material, which was the same as the steel material used in Example 1, was used for the evaluation test.

[0103] In Comparative Example 2, a pin-shaped steel material having a manganese phosphate coating not containing copper was obtained by the same method as in Example 1 except that the pin-shaped steel material was immersed in a manganese phosphate treatment solution (PF-M5: manufactured by Nihon Parkerizing Co., Ltd.) to which copper (II) nitrate was not added at a treatment temperature of 85 to 90° C. and a treatment time of 10 minutes.

[0104] In Comparative Example 3, a manganese phosphate coating (PF-M1A: manufactured by Nihon Parkerizing Co., Ltd.) was used as a manganese phosphate treatment solution without adding copper (II) nitrate as in Comparative Example 2 to obtain a pin-shaped steel material having a thick manganese phosphate coating containing no copper.

[0105] In Comparative Example 5, a coating liquid containing molybdenum disulfide and graphite as solid lubricants, polyamide-imide as an organic binder, and epoxy resin as a curing agent was further applied to the surface of the manganese phosphate coating shown in Comparative Example 2, and then the coated steel material was calcined at 120°C to form a calcined film, thereby obtaining a pin-shaped steel material having a solid lubricating film. The solid lubricating film obtained by this method has a film thickness of 10 to 15 μm.

[0106] [Table 1]

[0107]

[0108] (Determination of film thickness)

[0109] The film thickness of each coating of each embodiment and comparative example was measured as follows. A steel sample with a coating formed on the surface was cut perpendicularly to the coating, the cut sample was embedded in resin and cured, and ground with abrasive paper to expose the cross section of the coating. The sample with mirror-finished cross section was magnified and observed with a scanning electron microscope to measure the film thickness. The observation conditions of the scanning electron microscope are shown below.

[0110] SEM magnification observation measurement conditions

[0111] Testing machine: Electron microscope JSM-6510LA manufactured by JEOL Ltd.

[0112] Accelerating voltage: 15 kV

[0113] Detection electrons: Reflected electrons

[0114] Observation magnification: 2000 times

[0115] The film thickness was measured by magnified observation using a scanning electron microscope as follows. The distance between two points on the film that are opposite to each other in the magnified observation image, that is, two points on an imaginary line perpendicular to the film surface, was measured at five locations included in one field of view, and the average value of these distance values ​​was calculated and used as the film thickness value of the film (see Figure 1 ). That is, Figure 1 As shown, a sample having a copper-containing manganese phosphate coating 12 formed on the surface of a steel material 10 is embedded in an embedding resin 22, and then the exposed coating cross section of the sample is observed to measure the film thickness of the coating 12. It should be noted that the film thickness of the coating can also be measured by a simple film thickness measurement method using an electromagnetic film thickness meter.

[0116] (Measurement of surface roughness (Ra value / Rsk value))

[0117] The surface roughness values ​​(Ra value / Rsk value) of the outermost surface of the manganese phosphate coating in the steel materials of each Example and Comparative Example and the base material after wet peeling of the manganese phosphate coating were measured under the following conditions.

[0118] Measuring instrument: SURFCOM 1400G-12 manufactured by Tokyo Seimitsu Co., Ltd.

[0119] Stylus: Conical 60° and tip diameter 2μm

[0120] Standard: JIS B 0601:2001

[0121] Measurement type: Roughness measurement

[0122] Measuring speed: 0.3mm / s

[0123] Evaluation length: 4.000mm

[0124] Reference length: 0.8mm

[0125] λs filter: Yes

[0126] λs cut-off wavelength: 2.5μm

[0127] Cutoff type: Gaussian

[0128] Cut-off wavelength (λc): 0.8mm

[0129] Shape Removal: Least Squares Line

[0130] (Determination of Cu and Mn Contents in the Film (Sliding Surface))

[0131] The amounts of Mn and Cu in each film were measured by fluorescent X-ray measurement of each film of each Example and Comparative Example. The conditions of the fluorescent X-ray measurement are as follows.

[0132] Testing machine: Made by Rigaku Corporation

[0133] Fluorescence X-ray Analyzer RIX2100

[0134] Test conditions: voltage 50kV

[0135] Current value 50mA

[0136] Measuring diameter φ10mm

[0137] The content of Cu and Mn in the coating based on fluorescent X-ray under the above conditions was determined as follows. A calibration curve was prepared in advance based on the X-ray intensity of each component in the coating of each component and the coating analysis results obtained by ICP-AES based on wet stripping. Based on the prepared calibration curve, the quantitative analysis of each component in the coating of each embodiment and comparative example as an unknown sample was performed. The Mn content (g / m 2 )、Cu content (g / m 2 ) and the content ratio of Cu / Mn are shown in the above Table 1.

[0138] In addition, the method for measuring the content of Cu and Mn in the coating is not limited to the above-mentioned method using fluorescent X-rays, and other methods can be used to measure the content of each component of Cu and Mn. For example, the content of each component in the coating can be measured using methods such as atomic absorption spectrometry (AAS) based on wet stripping and ICP emission spectrometry (ICP-AES).

[0139] (Sliding performance test (friction and wear properties: FALEX test))

[0140] In order to evaluate the friction and wear properties of each embodiment and comparative example, a FALEX test was performed. The FALEX test is a Pin & Vee-Block type friction and wear test. Figure 2 The FALEX test machine 30 is shown in the schematic diagram of FIG. In the FALEX test, the journal pin (pin-shaped steel sample) 32 of each embodiment or comparative example is rotated while being clamped by two V-shaped blocks 34 as shown by the arrows in the figure. Then, the sliding friction and wear characteristics of the pin-shaped steel under line contact are evaluated while the load is linearly increased. When a sharp increase in the torque value is confirmed, it is determined that seizure has occurred and the test is stopped.

[0141] The conditions of the FALEX test are as follows.

[0142] Testing machine: Pin&Vee Block friction and wear testing machine (made by Sanyo Trading Co., Ltd.: F1500SP)

[0143] Speed: 290rpm

[0144] Sliding speed: 0.1m / s

[0145] Load increase speed: 0.05kN / s

[0146] Maximum load: 20kN

[0147] Lubrication environment: ATF (DW-1): immersed in oil

[0148] Oil temperature: The temperature at the start of the test was set to 10°C to 25°C. During the test evaluation, the temperature was measured with sliding heat generation.

[0149] Pin material: Steel samples of Examples and Comparative Examples

[0150] (SCM415 carburizing, quenching and tempering + surface treatment (excluding comparative example 1)

[0151] V block material: SCM415 carburized quenched and tempered

[0152] As the result of the FALEX test of each embodiment, comparative example, etc., the value of the maximum load until sintering occurs due to the rapid increase of the torque value (sintering load value) is measured. It should be noted that the sintering load value is measured using the above-mentioned friction and wear tester. In the above-mentioned Table 1, the evaluation results based on the following criteria are shown.

[0153] (Evaluation results of sliding friction and wear resistance)

[0154] Good: Sintering load value is 15kN or more

[0155] Slightly bad: sintering load value exceeds 10kN and is less than 15kN

[0156] Bad: sintering load value is less than 10kN

[0157] According to the results in Table 1 above, it is clear that when the manganese content is more than 0.89 g / m 2 And 2.1g / m 2 As described above, in Examples 1 to 5 in which the copper-containing manganese phosphate coating was provided so that the copper / manganese content ratio was within the range of 0.03 to 2.50, it was confirmed that the seizure resistance was excellent compared with Comparative Examples 1 to 4 which did not satisfy any of these conditions. Furthermore, by using the coating having such excellent seizure resistance, high durability such as high friction and wear resistance and fatigue resistance can be achieved.

[0158] Furthermore, it is considered that the surface roughness Ra of the base material is 0.16 μm or more, Rsk is -1.01 or less, and the film thickness of the coating is 1.4 μm or more, which also contributes to the realization of the above-mentioned excellent characteristics.

[0159] It was also confirmed that in Comparative Example 5 in which a solid lubricating film was formed by a calcining step, good seizure resistance was also exhibited, but according to Examples 1 to 5, a calcining step for forming a solid lubricating film was not required, and a sliding surface excellent in seizure resistance and the like could be achieved by a simple production method.

[0160] (Evaluation of Thermal Diffusivity)

[0161] In order to evaluate the heat dissipation characteristics of Example 1, Example 3 and Comparative Example 3, the thermal diffusivity (mm 2 The conditions for the thermal diffusivity measurement are as follows.

[0162] Measurement method: Laser flash method

[0163] Measuring device: LFA467 Hyper Flash manufactured by NETZSH Japan

[0164] Laser voltage: 150V

[0165] Pulse width: 0.2ms

[0166] Sample size: 10mm×10mm

[0167] Sample thickness: A film was formed on the surface of a 0.8 mm test piece (SPCC), and actual measurement was performed using a micrometer for each test object.

[0168] Measurement temperature range: room temperature (25°C), 100°C and 150°C

[0169] Number of measurements: n3 (3 measurements for each measurement temperature)

[0170] The results of thermal diffusivity measurement are shown below. That is, when the values ​​of thermal diffusivity in Examples 1 and 3 and Comparative Example 3 were measured (n3 average value), and the ratio of the thermal diffusivity of Comparative Example 3 to that of Examples 1 and 3 was calculated, the values ​​of thermal diffusivity and the ratio (relative ratio of the value of the Example / the value of the Comparative Example) are shown in the following Table 2. As can be seen, Examples 1 and 3, which were provided with a copper-containing manganese phosphate film, had a larger value of thermal diffusivity than Comparative Example 3, which was provided with a copper-free manganese phosphate film.

[0171] [Table 2]

[0172]

[0173] From the results in Table 2, it can be confirmed that the thermal diffusivity of the copper-containing manganese phosphate film of the example is 1.03 times or more that of the manganese phosphate film not containing copper in each temperature range of room temperature 25°C, 100°C and 150°C. Thus, it can be said that the copper-containing manganese phosphate film in the example has a high heat dissipation property.

[0174] Description of Reference Numerals

[0175] 10Steel

[0176] 12 coating (copper-containing manganese phosphate coating)

[0177] 14 Copper precipitated in coating 12

[0178] 16 Manganese phosphate coating area in coating 12

[0179] 22 Landfill resin

[0180] 30FALEX testing machine

[0181] 32 Journal pin (pin-shaped steel specimen)

[0182] 34 Block (V-block shaped steel specimen)

Claims

1. A combined sliding member comprising a first sliding member and a second sliding member formed of a steel material and sliding against each other, At least one of the sliding surfaces of the first sliding member and the second sliding member that slide against each other has a manganese phosphate coating containing copper, and the manganese content in the manganese phosphate coating is 0.89 g / m 2 Above, the copper / manganese content ratio is 0.03 to 2.50, The arithmetic mean roughness Ra of the surface of the base material on which the sliding surface having the manganese phosphate film is provided is 0.16 μm or more.

2. The combined sliding member according to claim 1, wherein: The manganese phosphate coating has a thickness of 1.4 μm or more.

3. The combined sliding member according to claim 1, wherein: The skewness Rsk of the surface of the base material is -1.01 or less.

4. The combined sliding member according to claim 1, wherein: The manganese content is 2.1 g / m 2 above.

5. The combined sliding member according to claim 3, wherein: The skewness Rsk of the surface of the base material is -1.78 or less.

Citation Information

Patent Citations

  • Sliding member

    JP1992175442A

  • Swash plate tilting mechanism for compressor

    JP2005351099A